Modeling Women in the Legal System of Iran - Mohammad Ghasem Tangestani; Faezeh varmazyar (پژوهشهای حقوقی)
Modeling has become popular in many societies today as one of the advertising arms of the fashion industry. Women are one of the important elements in this activity. Women's modeling has become one of the most challenging issues with the expansion of cyberspace in Iran. This research, by taking a descriptive-analytical method with a practical purpose and by collecting information from library and Internet sources, seeks to explain the gaps in the field of women's modeling in the Iranian legal system and to provide related proposals. This is done by examining the licenses, restrictions, and prohibitions of women's modeling in Iranian law. Based on the findings of this study, in the Iranian legal system, specific rules and regulations for Women's modeling are not specifically provided. Of course, there are rules and regulations in the fields of fashion and clothing, advertising, and cyberspace, which may include some types of modeling. From the present study, it can be concluded that the Iranian legal system does not have a specific approach to modeling and the legal gap in this regard is tangible. The recent reality has caused Women's modeling, which has emerged as a social phenomenon, to lead to undesirable results if not guided and monitored properly.